1988
DOI: 10.1002/hep.1840080623
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol-induced increase in cytosolic estrogen receptors in human male liver: A possible explanation for biochemical feminization in chronic liver disease due to alcohol

Abstract: The hepatic cytosolic estrogen receptor content was measured in liver samples from patients with normal livers and from patients with nonalcoholic cirrhosis, alcoholic cirrhosis and alcoholic hepatitis. The estrogen receptor content of normal liver was 5.2 +/- 3.5 fmoles per mg of cytosolic protein. Levels which were not significantly different from this were found in the samples from patients with nonalcoholic cirrhosis (2.1 +/- 2.0 fmoles per mg of cytosolic protein). The cytosolic estrogen receptor content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1
1

Year Published

1990
1990
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 25 publications
2
21
1
1
Order By: Relevance
“…39 For example, some evidence from human studies showed only an increased cytosolic ER protein in patients with active alcoholic liver disease and current drinking, but a determination of nuclear ER activity was not performed. 38 In summary, our data suggest that alcohol induces an early and profound reduction of serum testosterone levels, which further results in loss of androgen-regulated hepatic functions such as estrogen-metabolizing enzyme activity and the activity of androgen receptors. Such alcohol-induced hypogonadism precedes the changes in hepatic sex hormone homeostasis and subsequent feminization in male rats.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…39 For example, some evidence from human studies showed only an increased cytosolic ER protein in patients with active alcoholic liver disease and current drinking, but a determination of nuclear ER activity was not performed. 38 In summary, our data suggest that alcohol induces an early and profound reduction of serum testosterone levels, which further results in loss of androgen-regulated hepatic functions such as estrogen-metabolizing enzyme activity and the activity of androgen receptors. Such alcohol-induced hypogonadism precedes the changes in hepatic sex hormone homeostasis and subsequent feminization in male rats.…”
Section: Discussionmentioning
confidence: 64%
“…This delay of the serum increase in ceruloplasmin may suggest that hypogonadism precedes an expression of liver feminization. This apparently discrepant relationship between serum estrogen levels and activity of hepatic estrogen receptors reflects already existing different opinions about ER activity in alcoholic liver disease 10,[36][37][38][39] that may result from difficulties in comparing experimental animal models and human studies, insufficient data from animal models, and variability of findings in human studies. 39 For example, some evidence from human studies showed only an increased cytosolic ER protein in patients with active alcoholic liver disease and current drinking, but a determination of nuclear ER activity was not performed.…”
Section: Discussionmentioning
confidence: 99%
“…The hyperestrogenemia commonly seen in male alcoholic cirrhosis adds to the complexity of this relationship. It has been shown that prolonged ethanol consumption induces an increase in the hepatic estrogen receptors in males, especially in patients with alcoholic hepatitis (Villa et al, 1988). However, our study was not powerful e n o u g h d u e to the very small number of HCC patients who were carriers-to study the interaction between cirrhosis or alcohol and HBsAg or any interaction of risk factors with sex.…”
Section: Discussionmentioning
confidence: 80%
“…Moderate to high ethanol intake is also reported to influence sex hormone levels in men; in particular, plasma testosterone levels decrease, probably via alcohol-induced inhibition of testosterone (18). In addition, ethanol induces an increase in cytosolic ER in the human male liver, a possible explanation for feminization in chronic liver disease due to alcohol (19). However, the influence of such variations in endogenous sex hormone levels and ER on cardiovascular physiology in men with obesity or chronic liver disease is unknown.…”
Section: Evidence Of a Role For Endogenous Estrogens In Menmentioning
confidence: 94%